Out-of-pocket spending for contraceptives in Latin America. Issue 2 (17th December 2020) - Garraza, Lucas Godoy; Tobar, Federico; Rodríguez Bernate, Iván
Abstract: Despite progress in increasing the use of modern contraceptives in most Latin American countries over the last few decades, important challenges remain, including the heavy reliance on out-of-pocket spending to access contraceptives, which may expose consumption to macroeconomic fluctuations. Out-of-pocket spending on contraceptives and/or the proportion of women aged 15–49 who received free contraceptives at a public health facility or as part of statutory health insurance were estimated for 13 Latin American countries using the most recently available household budget surveys and demographic and health or similar household surveys. Data on contraceptive retail sales in 12 countries over the 2006–2010 period and publicly available macroeconomic indicators were used to examine the relationship between changes in sales and macroeconomic indicators using multiple regression models. On average, women aged 15–49 spent close to US$1 per month out-of-pocket on contraceptives. However, almost three out of five women received them free of charge. A 1% increase in the percentage of the population living on less than US$ 3.2/day (2011 PPP values), or the percentage unemployed in the labour force, predicted about a 2% decrease in the growth of contraceptive retail sales (measured in couple-years of protection, CYP, per capita) the subsequent year. The analysis revealed the sensitivity of contraceptive retail sales to changes in macroeconomic variables, particularly changes in poverty levels. Achieving universal access to family planning by 2030 will require improving contraceptive financing schemes.